Apoptosis‐Related Protein Expression During Pre‐ and Post‐Natal Testicular Development After Administration of Glucocorticoid in utero in the Sheep. Issue 5 (15th March 2013) - Pedrana, G; Viotti, MH; Souza, E; Sloboda, D; Martin, GB; Cavestany, D; Ortega, HH
Contents: Pre‐natal glucocorticoids are used in women at risk of preterm delivery to induce foetal lung maturation. However, glucocorticoids can produce negative outcomes for other tissues such as the reproductive system. We therefore tested the effects of pre‐natal betamethasone on testicular morphology and apoptotic protein immune expression during pre‐ and post‐natal development. Pregnant ewes (n = 42) bearing singleton male foetuses were randomly allocated to receive intramuscular injections of saline or betamethasone (0. 5 mg/kg) at 104, 111 and 118 days of gestation (DG). Testes were collected at 121 and 132 DG, and at 45 and 90 post‐natal days (PD) and subjected to morphometric analysis (volume densities of sex cords and interstitial tissues; sex cord diameter). Immunohistochemistry (% stained area) was used to assess active caspase‐3, Bax, Bcl‐2 and cell‐cycle proteins (PCNA). Compared with control values, betamethasone treatment decreased sex cord diameter at 121 DG, 45 and 90 PD, and sex cord volume at 90 PD. Active caspase‐3 was decreased by betamethasone at 121 DG and 90 PD, but Bax was increased in all betamethasone groups. Bcl‐2 and PCNA decreased in the betamethasone groups at 121 DG and 45 PD, but increased at 132 DG and 90 PD. We conclude that high levels of pre‐natally administered glucocorticoid reduce foetal testicular development, perhaps via changes in the balance between pro‐ and anti‐apoptotic proteins and cell‐cycle proteins. These outcomes could compromise the future spermatogenic potential of male offspring.